Pathological internet use is on the rise among european adolescents - Kaess, Michael; Parzer, Peter; Brunner, Romuald; Koenig, Julian; Resch, Franz (Journal of adolescent health, 2016)
Purpose Increased Internet accessibility has been accompanied by an increased awareness of pathological Internet use (PIU). The aim of the study was to investigate a potential increase of PIU among European adolescents. Methods Comparable data from two large cross-sectional multicentre, school-based studies conducted in 2009/2010 and 2011/2012 in five European countries (Estonia, Germany, Italy, Romania, and Spain) were used. The Young's Diagnostic Questionnaire was used to assess the prevalence of PIU. Results The comparison of the two samples provides evidence that the prevalence of PIU is on the rise (4.01%-6.87%, odds ratio = 1.69, p < .001) except in Germany. Comparison with data on Internet accessibility suggests that the rise in prevalence of adolescent PIU may be a consequence of increased Internet accessibility. Conclusions Our findings are the first data to confirm the rise of PIU among European adolescents. They definitively warrant further efforts in the implementation and evaluation of preventive interventions.